THE RELATIONSHIP BETWEEN EDUCATION, JOB SATISFACTION, AND WORK MOTIVATION TO WORK PRODUCTIVITY (INVESTIGATION ON WORKERS IN THE WELDING SECTION OF RACK PRODUCTION AT UD. KING RACK, SURABAYA, INDONESIA) - Ni'matul Mawaddah; Indriati Paskarini (The Indonesian Journal of Public Health, 2021)
ABSTRACTUD. King Rack Surabaya is a rack production home industry. The production process includes welding of the rack structure. This study aims to analyze the relationship between education, job satisfaction, and work motivation to the work productivity of workers in the welding section of rack production at UD. King Rack, Surabaya, Indonesia. This is an observational study with a cross-sectional design. The study sample used a total population of 12 workers. Data were taken in the form of primary data tested with the Spearman correlation test. The results of the analysis show that the majority of respondents graduated from elementary school and the majority of respondents' job satisfaction was high. However, majority of respondents' work motivation was moderate and the majority of respondents' work productivity was low. The results of the Spearman correlation analysis indicate a relationship between education and work productivity (correlation coefficient = 0.475) as well as work motivation and work productivity (coefficient correlation = 1.000). There was no relationship between job satisfaction and work productivity. To increase work productivity, daily standards for the number of racks to be produced by workers need to be set. Besides that, it is important to give praise and appreciation to the workers in order for them to produce racks that are above the work standard. Keywords: education, job satisfaction, work motivation, work productivity